Warehouse Inventory System With Min Max Stock And QR Code Method In One Of The Printing Companies - Ririn Putri Pratiwi; Marjito Marjito; Farhanah Fitria Mustari; Dian Kencana (Informatics Management, Engineering and Information System Journal, 2026)
The swift advancement of computer-based information systems has markedly enhanced the efficacy of many operational tasks within organizations, especially in inventory management, which necessitates precision and efficiency. A printing company continues to rely on a manual system for documenting incoming and outgoing goods, retrieving item information, and overseeing stock levels, leading to frequent delays, inaccuracies, and inefficient workflows. This study formulates a comprehensive warehouse inventory system that uses the Min-Max Stock approach as a regulatory framework to establish minimum and maximum inventory thresholds, thereby averting shortages and excess stock. The system incorporates QR Code technology to enhance item identification, streamline recording, and deliver detailed item information. The deployment of this system is anticipated to improve operational efficiency, minimize recording errors, expedite data retrieval operations, and facilitate more precise decision-making in stock management at the printing company.